Improved setpoint adjustment for ultrasonic motors - Schulte, Thomas; Fröhleke, Norbert (Proceedings of International Conference on Advanced Intelligent Mechatronics)
Speed control strategies for piezoelectric drives have been presented by several authors. Beside various control strategies based on adaptive structures like MIAS, MRAS, neural nets or fuzzy control, a completely model based control system using an inner bending wave control and an outer speed control including a torque calculator for linearization has been presented. The paper deals with investigations and improvements of this torque calculator. The setpoint adjustment is focused to utilize the degrees of freedom for the bending wave values, which represents an additional potential for optimization of the performance of the drive system. Theoretical and experimental results confirm the advances.